Diseño y construcción de un prototipo de máquina para corte y grabado láser por control numérico - Bermúdez Morán, Bryan (2022)
This project focused on the analysis of the pyrography process, which is an artisanal technique for making sketches, engraving diagrams on wood surfaces, etc. On the other hand, the research was in the canton of Buena Fe, where information was collected at the locality level to establish technical requirements, such as the mechanical architecture that makes up the drive systems, structure, mechanical components and in turn, the electrical architecture that presents the connection and communication system. Where a control of the development methodology was carried out, defining the user requirements through a survey, establishing the requirements of the system and its architecture. As for the design process, it developed the analysis of shafts with diameters of 10 mm and 8 mm, selection of NEMA 17 motors with maximum torque of 0.4 Nm, selection of bearings, selection of spindle and nuts. Therefore, they complied with the design requirements established in bibliographic references and documentation. Subsequently, the construction of the prototype of general dimensions of 750 x 535 mm was carried out, which consists of components made by 3D additive manufacturing, it was also characterized by its laser power of 15 W with a power supply of 110 to 220 V to manipulate the Arduino Uno board. Finally, the test protocol was developed, which consisted of executing the main functions of the engraving or cutting equipment, therefore, operating conditions are established for each of the materials tested (plywood, MDF, cardboard, balsa, cardboard straw), so that in each test variations of speeds, power, image quality, equipment limitations can be found, whose results denote operating parameters at minimum speeds of 20 mm/min for cutting and 900 mm/min as maximum speed for engraving. Keywords: Laser engraving and cutting, CNC Control, Arduino Uno, GRBL, G Code